Tracing modernity : manifestations of the modern in architecture and the city - Hvattum, Mari, 1966-; Hermansen Cordua, Christian (Routledge, 2004)
Drawng on architectural and urban history as well as philosophy and sociology, the book outlines the complex and conflicting roots of modernity by tracing its manifestations in architecture and the city.